Pengaruh profitabilitas, likuiditas, solvabilitas terhadap harga saham - Idris Ramadhani (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2018)
The research objective is to analyze the effects of profitability, liquidity, and solvency on stock prices. Data were collected using purposive sampling method, the samples that meet the criteria are 43 manufacturing companies listed on IDX in the period 2013-2017. Through the panel data regression analysis shows that profitability and solvency have no significant effect on stock prices, but liquidity has a significant effect on stock prices. Practical implications for investors and companies are discussed in this paper.